Assessment of Managerial Innovation in Company X Using Fuzzy AHP - Sitonga, Roland YH; Setiawati, Marla; Gratianus, Theodorus (RSF Conference Series: Business, Management and Social Sciences, 2022)
Company X is an Indonesian dairy company with a significantly large market share. The successes of its product innovation are highly linked with its managerial function, which indicates the existence of innovation in its company management. The company should understand the level of its managerial innovation and utilize its potential to produce product innovations continuously. This research aims to determine the company’s level of managerial innovation to support product innovation accomplishments. The study utilizes two methods in determining managerial innovation levels. The first method is by measuring employee perception of managerial functions of the company through a survey. The second method is through direct observation of executive activities related to managerial functions using a prearranged observation protocol. The final managerial innovation score will be calculated using the Fuzzy AHP method. The study found that the company’s managerial innovation level reached 57%, which is a relatively high level. The study also found that leading function is very innovative, while organization function should be improved to support better product innovations.